Age-Related Differences in Cardiac Ischemia-Reperfusion Injury: Effects of Estrogen Deficiency - Korzick, D.H. (2013)
Despite conflicting evidence for the efficacy of hormone replacement therapy in cardioprotection of postmenopausal women, numerous studies have demonstrated reductions in ischemia/reperfusion (I/R) injury following chronic or acute exogenous estradiol (E(2)) administration in adult male and female, gonad-intact and gonadectomized animals. It has become clear that ovariectomized adult animals may not accurately represent the combined effects of age and E(2) deficiency on reductions in ischemic tolerance seen in the postmenopausal females. E(2) is known to regulate the transcription of several cardioprotective genes. Acute, non-genomic E(2) signaling can also activate many of the same signaling pathways recruited in cardioprotection. Alterations in cardioprotective gene expression or cardioprotective signal transduction are therefore likely to result within the context of aging and E(2) deficiency, and may help explain the reduced ischemic tolerance and loss of cardioprotection in the senescent female heart. Quantification of the mitochondrial proteome as it adapts to advancing age and E(2) deficiency may also represent a key experimental approach to uncover proteins associated with disruptions in cardiac signaling contributing to age-associated declines in ischemic tolerance. These alterations have important ramifications for understanding the increased morbidity and mortality due to ischemic cardiovascular disease seen in postmenopausal females. Functional perturbations that occur in mitochondrial respiration and Ca(2+) sensitivity with age-associated E(2) deficiency may also allow for the identification of alternative therapeutic targets for reducing I/R injury and treatment of the leading cause of death in postmenopausal women.